2014
DOI: 10.1002/2014gl060953
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic control of equatorial plasma bubble activity modeled by the TIEGCM with Kp

Abstract: Describing the day‐to‐day variability of Equatorial Plasma Bubble (EPB) occurrence remains a significant challenge. In this study we use the Thermosphere‐Ionosphere Electrodynamics General Circulation Model (TIEGCM), driven by solar (F10.7) and geomagnetic (Kp) activity indices, to study daily variations of the linear Rayleigh‐Taylor (R‐T) instability growth rate in relation to the measured scintillation strength at five longitudinally distributed stations. For locations characterized by generally favorable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 43 publications
4
84
0
Order By: Relevance
“…It is well known that the PRE strength is an important parameter in controlling the growth of EPBs (e.g., Abdu et al 1981;Tulasi Ram et al 2006;Su et al 2008;Carter et al 2014a) and that the PRE itself can exhibit a strong daily variability (e.g., Scherliess and Fejer 1999). Figure 6 showed that the plasma above the BCL ionosonde rose significantly faster on the evening of 28 July compared to the rest of the month.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is well known that the PRE strength is an important parameter in controlling the growth of EPBs (e.g., Abdu et al 1981;Tulasi Ram et al 2006;Su et al 2008;Carter et al 2014a) and that the PRE itself can exhibit a strong daily variability (e.g., Scherliess and Fejer 1999). Figure 6 showed that the plasma above the BCL ionosonde rose significantly faster on the evening of 28 July compared to the rest of the month.…”
Section: Discussionmentioning
confidence: 95%
“…A series of recent works have examined the daily EPB occurrence during peak EPB season with the use of the Thermosphere Ionosphere Electrodynamics General Circulation Model (Carter et al 2014a;. In these works, the daily variability during peak season was captured by the identification of evenings with decreased EPB growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some efforts have been made in the attempt to predict EPB structures and/or scintillation (e.g., Retterer et al, 2005;Retterer, 2005;Kelley and Retterer, 2008;Rezende et al, 2010;Redmon et al, 2010;Carter et al, 2014a, b;Sousasantos et al, 2017). These works essentially deal only with the existence (or nonexistence) of EPB structures and/or scintillation; however, according to the results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The F region boundary is set at 200 km. The recombination rate is assumed to be zero as in Carter et al [2014a]. Because the upper limit of the TIEGCM is at about 500 km, the field line can reach roughly15°magnetic latitudes in both north and south.…”
Section: Model Calculation Of Growth Ratementioning
confidence: 99%
“…For example, Luo et al [2012] used International Reference Ionosphere and horizontal wind model to calculate the growth rate. Recently, Carter et al [2014aCarter et al [ , 2014b used the Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) to calculate the R-T growth rate and successfully showed that the R-T rate is affected by geomagnetic activity. Because the TIEGCM is a comprehensive ionosphere model with many options, more can be done with the model to calculate the R-T growth rate.…”
Section: Introductionmentioning
confidence: 99%